FRETS-VWF73 rather than CBA assay reflects ADAMTS13 proteolytic activity in acquired thrombotic thrombocytopenic purpura patients - Mancini, Ilaria; Valsecchi, Carla; Lotta, Luca Andrea; Deforche, Louis; Pontiggia, Silvia; Bajetta, Mariateresa; Palla, Roberta; Vanhoorelbeke, Karen; Peyvandi, Flora (Thrombosis and Haemostasis, 2014)
Collagen-binding activity (CBA) and FRETS-VWF73 assays are widely adopted methods for the measurement of the plasmatic activity of ADAMTS13, the von Willebrand factor (VWF) cleaving-protease. Accurately assessing the severe deficiency of ADAMTS13 is important in the management of thrombotic thrombocytopenic purpura (TTP). However, non-concordant results between the two assays have been reported in a small but relevant percentage of TTP cases. We investigated whether CBA or FRETS-VWF73 assay reflects ADAMTS13 proteolytic activity in acquired TTP patients with non-concordant measurements. Twenty plasma samples with non-concordant ADAMTS13 activity results, <10% using FRETS-VWF73 and ≥20% using CBA, and 11 samples with concordant results, <10% using either FRETS-VWF73 and CBA assays, were analysed. FRETS-VWF73 was performed in the presence of 1.5 M urea. ADAMTS13 activities were also measured under flow conditions and the VWF multimer pattern was defined in order to verify the presence of ultra-large VWF due to ADAMTS13 deficiency. In FRETS-VWF73 assay with 1.5 M urea, ADAMTS13 activity significantly increased in roughly 50% of the samples with non-concordant results, whereas it remained undetectable in all samples with concordant measurements. Under flow conditions, all tested samples showed reduced ADAMTS13 activity. Finally, samples with non-concordant results showed a ratio of high molecular weight VWF multimers higher than normal. Our results support the use of FRETS-VWF73 over CBA assay for the assessment of ADAMTS13 severe deficiency and indicate urea as one cause of the observed differences.
Keywords: ADAMTS13 activity assay; TTP; autoantibodies; von Willebrand factor; flow assay